Choosing a Lecture Format in Higher Pharmaceutical Education - Tatiana Semenova; Susanna Sologova; Sergey Zavadsky; Ekaterina Grigorevskikh; Arus Margaryan; Daria Trashchenkova; Esma Avakyan; Dmitry Sokhin; Tatiana Litvinova; Elena Smolyarchuk (Вопросы образования, 2022)
The forced massive transition of universities to distance learning due to the pandemic has raised questions about the effectiveness of online education in general and video lectures in particular. Research shows that video lectures are either comparable or less effective than face-to-face lectures. In this work, based on the data collected as part of the experiment, we compare two lecture formats (videolecture and face-to-face lecture) based on the educational results of students, and also evaluate the combined lecture format. The experiment involved 151 second-year students in the direction of training “Pharmacy” of Sechenov University. The field experiment was carried out in the spring semester of the 2020-2021 academic year in three stages. At the first stage, some of the students listened to a face-to-face lecture, and some - a video lecture. At the second stage, both groups were swapped. At the final stage, both groups listened to a combined lecture. Our research has shown that a video lecture and a face-to-face lecture are the same in their effectiveness: on average, students received the same educational results as a result of mastering the lecture material. At the same time, the combined lecture led to an increase in the educational results of students - after the combined lecture format, students received a higher score for the post-test, and also showed a greater increase in the level of knowledge. The results of the study will be especially relevant for the administration of universities responsible for the implementation of online learning, and teachers who conduct lectures.